The Role of Inherent Concepts of Design Thinking in Industrial Design Education - Samira Ashari; Hassan Sadeghi Naeini (Revista Eídos)
Design, as a human capability to shape society for addressing needs and imbuing life with meaning, is defined through the creation of products via empirical and analytical methods, where design thinking also serves as a methodology for the intellectual activity of generating creative ideas. Although design thinking has long been recognized as a foundation for design and aids researchers, education must not be overlooked as the core and driving force of research and deserves attention. Given that industrial design encompasses various domains, enhancing its educational level can cover diverse approaches. However, what must not be forgotten is the role of inherent design concepts in its education. To improve the quality of education and enhance the capabilities of industrial designers, it is essential to consider inherent design concepts in these educational programs, one of the best ways to understand which is to examine the perspectives of leading pioneers in the field and their studies. This research aims to explore the place of inherent design concepts in industrial design educational resources. A descriptive method with a qualitative approach was used for this research, through the collection of documentaries (library-based) information. The findings reveal that researchers have identified fifteen intrinsic aspects of design, with Bryan Lawson and Nigel Cross conducting the most studies on these concepts, highlighting the significance of the position of inherent design concepts in industrial design education.